2018
DOI: 10.1109/tit.2018.2822660
|View full text |Cite
|
Sign up to set email alerts
|

How Compressible Are Innovation Processes?

Abstract: The sparsity and compressibility of finite-dimensional signals are of great interest in fields such as compressed sensing. The notion of compressibility is also extended to infinite sequences of i.i.d. or ergodic random variables based on the observed error in their nonlinear k-term approximation. In this work, we use the entropy measure to study the compressibility of continuous-domain innovation processes (alternatively known as white noise). Specifically, we define such a measure as the entropy limit of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This is achieved by compound-Poisson processes and also by Laplace processes, that are therefore the sparsest processes. These results are coherent with recent works of H. Ghourchian et al in their recent works on the entropy of sparse processes [26]. Here, the authors have shown that, among SαS and compound Poisson white noises, the less sparse is the Gaussian white noise, and the sparsest are the compound Poisson white noises.…”
Section: Discussion and Examplessupporting
confidence: 93%
“…This is achieved by compound-Poisson processes and also by Laplace processes, that are therefore the sparsest processes. These results are coherent with recent works of H. Ghourchian et al in their recent works on the entropy of sparse processes [26]. Here, the authors have shown that, among SαS and compound Poisson white noises, the less sparse is the Gaussian white noise, and the sparsest are the compound Poisson white noises.…”
Section: Discussion and Examplessupporting
confidence: 93%
“…Linear In the second framework, one can quantify the compressibility of a Lévy process in the information theoretic sense through the entropy of the underlying Lévy white noise, as in [54]. These two frameworks are complementary and based on totally different tools, but they are consistent and lead to the same compressibility hierarchy.…”
Section: Brownian Motion Compound Poissonmentioning
confidence: 99%
“…For continuous-domain innovation processes (i.e., continuous-domain white noise), the notions of RID and RDE are defined in [10] by vanishingly fine quantization of the time axis and the amplitude range.…”
Section: Related Workmentioning
confidence: 99%
“…It is shown that when the distortion tends to zero, the limiting value of the RDF is closely related to the differential entropy (if it exists) [3]. The compressibility notations are not limited to discrete and continuous sources: there has been some recent efforts to define this notion for sequences [4], [5], [6] and random processes [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation